A review of the Ordovician acritarch genus Barakella Cramer & Díez 1977. (22nd December 2017) - Yan, Kui; Li, Jun; Molyneux, Stewart G.; Raevskaya, Elena G.; Servais, Thomas
ABSTRACT: The Ordovician acritarch genus Barakella Cramer & Díez 1977 and two species, B. felix and B. fortunata, bearing characteristic anastomosing filamentous elements at one pole were first described from the subsurface of the Kasba Tadla Basin, Morocco. Subsequently, another species was described from the South Chinese Ordovician and was later attributed to the genus as Barakella rara . New material from the type locality in Morocco and additional sections in South China are used for a review of the genus Barakella . Based on this review, including statistical analysis, Barakella rara is considered a junior synonym of Barakella felix . Barakella is a useful taxon for biostratigraphical applications in the Ordovician. Its first appearance datum (FAD) lies in the early Floian (Early Ordovician, time slices 2a–2b) in both South China and Wales. Except for a doubtful record from Sweden, all records of Barakella are from the peri-Gondwana margin, making the genus an indicator of the peri-Gondwana palaeoprovince. The appearance of Barakella in South China indicates that Barakella possibly originated in shallow-water nearshore environments, and later spread to offshore environments.